Inhibition of Fibrinolysis by Hyperlipemia - Cliffton, Eugene E.; Burchell, Albert R. (Thrombosis and Haemostasis, 1961)
1. Parenteral injection of triton produced inhibition of fibrinolysis; this phenomenon correlated with hyperlipemia produced by the triton.2. Triton induced hyperlipemia caused greater inhibition of fibrinolysis than did cholesterol feedings. It was suggested that this might be related to difference in cholesterol-phospholipid ratio.3. Saturated fat emulsions produced a greater degree of fibrinolytic inhibition than did unsaturated fat preparations.